DO MICRO SMALL MEDIUM ENTERPRISES (MSMES) NEED MODERN MANAGEMENT ACCOUNTING TECHNIQUES? AN INDONESIAN PERSPECTIVE - Amanda Acintya (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/Main Objectives: Management accounting practices (MAPs) have long been recognized as a subject of interest with regards to business performance, including for Micro Small Medium Enterprises (MSMEs). Despite the significant role of this sector in emerging countries, there is a dearth of research into the practical implementation of MAPs. Background Problems: The purpose of this paper is to gain a general understanding of whether modern and traditional MAPs, in the MSMEs’ context, are on an equal footing in terms of usage and perceived importance. We adopt the IFAC’s management accounting (MA) evolution model to structure this research. Novelty: This study contributes by tracing the adoption of MAPs as an indicator of the MSMEs’ need for MA information. Within an academic and regulatory framework, this study is believed to provide an important contribution for academicians, practitioners and the government. Research Methods: We conducted an attended survey of 34 MSMEs around Yogyakarta and used the simple yet meaningful statistical technique of descriptive analytics. Findings/Results: The findings indicate that traditional MAPs (the ones in IFAC stages 1 and 2) were found to be marginally better implemented than the modern MAPs (IFAC stages 3 and 4). We compute the difference of two proxies: extent of implementation (EI) and perceived importance (PI) as an indicator of the gap in their operationalization. We found that as the IFAC stage moves along to the modern MAPs spectrum, the average difference between EI-PI also moves up accordingly. Conclusion: Hence, despite the better implementation of traditional MAPs among the MSMEs, it does not eliminate the opportunity for the increasing usage of modern MAPs in the future.